Mathematical Modeling of Field Recital of Harrow in Clay – Loam Soil in South Eastern Nigeria - Okeke, C. G.; Oduma, O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
This research was carried out to model and optimize the efficiency of disc harrow on clay-loam soil in South – East Nigeria to assist farmers scrutinize and select appropriate harrowing implement reliant on soil type for efficacious and magnificent production. The harrowing operation was conducted at selected effective working widths, operational speeds and cutting depths using 2-gangs tandem disc harrow. The experimental design adopted in the research was a three level – three factor full factorial design. The experiment consists of three factors which were varied at three levels of harrowing depths which include 10, 20, 30 cm; three levels of effective working widths of 60, 120 and 180 cm and three levels of operational speeds (6, 7 and 8 km/hr). Central Composite Response Design which gives 17 test runs was performed for each sample. The results found that the highest field efficiency of 98.50% was obtained when the harrow was operated at the pulverizing depth of 20cm under operational speed of 7 kmh-1 and working width of 120 cm. The quadratic model equation was statistically significant (P ˂ 0.05) for the prediction of the field efficiency. Additionally, the results show that the coefficient of determination; R2 for the field efficiency was 0.9139, which indicated adequate correlations among the factors. The Predicted R² of 0.7695 was reliable with the Adjusted R² of 0.8031 which identified excellent interactions between the factors (effective working width, operational speeds and harrowing depths). The adequacy Precision (10.3749) obtained indicated seemly indicator and that the model could navigate the design space. The optimum field efficiency and the desirability of 96.66% and 0.697 were respectively attained at optimum depth of 30 cm, working width of 180 cm and speed of 6.16 kmh-1. Therefore, farm operators can henceforth, evaluate and select the harrow implements using the developed model.